Trends in collection, use and disclosure of personal information in contemporary health research: challenges for research governance - Willison, Donald J (Health law review, 2005)
Examines challenges arising in the governance of observational health research requiring the collection, use, and management of person-level data. With the advent of large health infostructures, the proliferation and decentralization of a larger number of smaller personal data holdings, and development of large multicentered registries and biobanks, come challenges related to "fuzzy boundaries" regarding the purposes for which the data are used and the role of the individual accessing the data; adequate data management in a decentralized research environment; institutional vs investigator accountability for safeguarding data; the role of consent; and engendering of public trust with respect to the use of personal information.